Nitrogen Can Alleviate the Inhibition of Photosynthesis Caused by High Temperature Stress under Both Steady-State and Flecked Irradiance - Guanjun Huang; Qiangqiang Zhang; Xinghai Wei; Shaobing Peng; Yong Li (Frontiers in Plant Science, 2017)
Nitrogen is one of the most important elements for plants and is closely related to photosynthesis. High temperature stress significantly inhibits photosynthesis under both steady-state and flecked irradiance. However, it is not known whether nitrogen can affect the decrease in photosynthesis caused by high temperature, especially under flecked irradiance. In the present study, a pot experiment was conducted under two nitrogen (N) supplies with rice plants, and the steady-state and dynamic photosynthesis rates were measured under 28 and 40°C. High temperature significantly increased leaf hydraulic conductance (Kleaf) under high N supply (HN) but not under low N supply (LN). The increased Kleaf maintained a constant leaf water potential (Ψleaf) and steady-state stomatal conductance (gs,sat) under HN, while the Ψleaf and gs,sat significantly decreased under high temperature in LN conditions. This resulted in a more severe decrease in steady-state photosynthesis (Asat) under high temperature in the LN conditions. After shifting from low to high light, high temperature significantly delayed the recovery of photosynthesis, which resulted in more carbon loss under flecked irradiance. These effects were obtained under HN to a lesser extent than under LN supply. Therefore, it is concluded that nitrogen can alleviate the inhibition of photosynthesis caused by high temperature stress under both steady-state and flecked irradiance.